Platelet chemokines in health and disease - Karshovska, Ela; Weber, Christian; Hundelshausen, Philipp von (Thrombosis and Haemostasis, 2013)
In recent years, it has become clear that platelets and platelet-derived chemokines, beyond their role in thrombosis and haemostasis, are important mediators affecting a broad spectrum of (patho)physiological conditions. These biologically active proteins are released from α-granules upon platelet activation, most probably even during physiological conditions. In this review, we give a concise overview and an update on the current understanding of platelet-derived chemokines in a context of health and disease.Note: The review process for this manuscript was fully handled by G. Y. H. Lip, Editor in Chief.
Keywords: Platelet immunology; chemokines; atherosclerosis; inflammation; infectious diseases